A Curriculum in Quality Improvement for Interprofessional Palliative Care Trainees. (January 2020) - Lakin, Joshua R.; Brannen, Elise N.; Bernacki, Rachelle E.; Jones, Emma
Introduction: A structured and intentional approach to quality improvement is critical for clinicians specializing in palliative care and is a required component of training programs. Methods: We present a multimodal, comprehensive curriculum for teaching quality improvement to interdisciplinary trainees in palliative care. Results: The curriculum consists of 4 sessions, one and half hours long a piece, that focus on the purpose and practice of quality improvement and guide learners through a team-based project implementation experience. Course assessments demonstrate satisfaction with the course and improvement in targeted skills, knowledge, and attitudes. Discussion: Several key learnings stand out from our experience with this curriculum as central to the experience of students: project work completed as interdisciplinary teams, varying teaching methodologies over a longitudinal curriculum, and the opportunity for formal presentation of their work.